(untitled) (Czech Journal of Multidisciplinary Innovations, 2025)
This article provides a scholarly analysis of the social-philosophical characteristics of modernization and the innovative development of society, the transition from traditional social life to a modern stage, and the profound transformations occurring across all spheres of social existence. The article argues that modernization and innovation represent processes through which societies move beyond traditional modes of living toward contemporary forms, resulting in deep changes across the social structure. It is demonstrated that modernization and innovation function as driving forces in building modern societies.